Enterprise Digital Transformation and Misallocation of Credit Resources - Ke, Zhenyu (Transactions on Economics, Business and Management Research, 2024)
Rational allocation of resources is the way to realize the high-quality development of China's economy. This paper empirically examines the impact of enterprise digital transformation on misallocation of credit resources using Chinese A-share listed companies in Shanghai and Shenzhen from 2007 to 2022 as the research samples. Baseline regression results show that there is a significant inhibitory effect of enterprise digital transformation development on misallocation of enterprise credit resources. Through the mediation analysis, it is found that improving the quality of enterprise internal controls, reducing the management of accrued surplus and lowering the cost of debt financing are effective paths for enterprise digital transformation to inhibit misallocation of enterprise credit resources. Further, the heterogeneity analysis based on the perspectives of enterprise micro characteristics and macro market environment shows that the non-state and high-tech attributes of enterprises and high marketization degree will strengthen the inhibitory effect of enterprise digital transformation on misallocation of enterprise credit resources. The findings are of great revelation to futher promote the rational allocation of credit resources under the enterprise digital transformation.